Role of Relational Capital and Social Capital in Mediating the Effect of Asta-Brata-Based Human Capital in Financial Performance - Ayu Mahanavami, Gusti; Wiksuana, Wiksuana; Anom Purbawangsa, I. B.; Rahyuda, Henny (Opción, 2019)
The purpose of this study was to examine and explain the effect of human capital, relational capital and social capital on the financial performance of Rural Credit Banks in Bali, both in direct and indirect relationships. This research used a positivism approach. The population in this study consisted of conventional BPRs in Bali Province, totaling 136 BPRs in Bali. The unit of analysis was 60 BPR leaders. Quantitative analysis based on multivariate analysis using structural equation modeling with Partial Least Square ap- proach). The results of the study provided an explanation of the important role of the mediation of relational capital and social capital as the full media- tion of Asta Brata-based human capital which has an impact on the financial performance of BPRs in Bali. The findings of this study were the two variables namely Relational Capital and Social Capital proved to be full mediation but the priority of determining the strategic path was through Relational Capital.